Treatment of helminth co-infection in individuals with HIV-1: A systematic review of the literature. - Judd L Walson; Grace John-Stewart (Public Library of Science (PLoS), 2007)
The HIV-1 pandemic has disproportionately affected individuals in resource-constrained settings. It is important to determine if other prevalent infections affect the progression of HIV-1 in co-infected individuals in these settings. Some observational studies suggest that helminth infection may adversely affect HIV-1 progression. We sought to evaluate existing evidence on whether treatment of helminth infection impacts HIV-1 progression.This review was conducted using the HIV/AIDS Cochrane Review Group (CRG) search strategy and guidelines. Published and unpublished studies were obtained from The Cochrane Library (Issue 3, 2006), MEDLINE (November 2006), EMBASE (November 2006), CENTRAL (July 2006), and AIDSEARCH (August 2006). Databases listing conference abstracts and scanned reference lists were searched, and authors of included studies were contacted. Data regarding changes in CD4 count, HIV-1 RNA levels, clinical staging and/or mortality were extracted and compared between helminth-treated and helminth-untreated or helminth-uninfected individuals.Of 6,384 abstracts identified, 15 met criteria for potential inclusion, of which 5 were eligible for inclusion. In the single randomized controlled trial (RCT) identified, HIV-1 and schistosomiasis co-infected individuals receiving treatment for schistosomiasis had a significantly lower change in plasma HIV-1 RNA over three months (-0.001 log(10) copies/mL) compared to those receiving no treatment (+0.21 log(10) copies/mL), (p = 0.03). Four observational studies met inclusion criteria, and all of these suggested a possible beneficial effect of helminth eradication on plasma HIV-1 RNA levels when compared to plasma HIV-1 RNA changes prior to helminth treatment or to helminth-uninfected or persistently helminth-infected individuals. The follow-up duration in these studies ranged from three to six months. The reported magnitude of effect on HIV-1 RNA was variable, ranging from 0.07-1.05 log(10) copies/mL. None of the included studies showed a significant benefit of helminth treatment on CD4 decline, clinical staging, or mortality.There are insufficient data available to determine the potential benefit of helminth eradication in HIV-1 and helminth co-infected adults. Data from a single RCT and multiple observational studies suggest possible benefit in reducing plasma viral load. The impact of de-worming on markers of HIV-1 progression should be addressed in larger randomized studies evaluating species-specific effects and with a sufficient duration of follow-up to document potential differences on clinical outcomes and CD4 decline.